Manners maketh man: An Analysis of the Song Translation Strategies in Sting's 'Englishman in New York' - Aramburuzabala Arrieta, Ibai; Adams, Heather (Technium Social Sciences Journal, 2025)
This paper undertakes an analysis of Sting's globally recognized 1987 song, "Englishman in New York," and its Spanish translation by Txus Bengoechea. The original lyrics offer a profound exploration of identity, individuality, and the experience of otherness within a foreign culture. This is exemplified through the figure of Quentin Crisp, an "Englishman in New York" who embodied multifaceted "alienation" – both geographic and social. The study is motivated by the inherent complexities of rendering a "singable" text from one language to another while preserving its core essence and nuanced message across linguistic and cultural borders. The theoretical framework integrates concepts of cultural and translational identity, drawing on perspectives that view identity as a dynamic process. The analysis also considers the legal and sociolinguistic implications of the term "alien". The study applies established theories of song translation, specifically Franzon's five strategic options for approaching lyrical adaptation and Low's Pentathlon Principle, which provides a practical framework for evaluating singable translations across multiple parameters. The methodology involves a line-by-line analysis of the juxtaposed original and translated lyrics, treating each line as a translation unit due to the inseparable nature of words and music in songs. This approach aims to identify the strategies employed in navigating the conflicting demands of musicality, naturalness, and semantic fidelity inherent in song translation.